Stock Prices and Financial Indicators in the Food and Beverage Industry: Harga Saham dan Indikator Keuangan di Industri Makanan dan Minuman - Purdiyani Purdiyani; Nurasik Nurasik (Academia Open, 2022)
This study investigates the influence of key financial indicators, namely Earnings Per Share (EPS), Debt to Equity Ratio (DER), and Price Earning Ratio (PER), on stock prices within the Food and Beverage industry listed on the Indonesia Stock Exchange (IDX) from 2016 to 2019. The research population comprised all Food and Beverage companies listed on the IDX during the specified period. By employing a partial t test analysis using SPSS version 25, a sample of 68 Consumer Goods Industry sector companies was selected, consisting of 17 Food and Beverage sector companies. The findings reveal that EPS significantly affects stock prices in Food and Beverage companies on the IDX. Conversely, DER does not demonstrate a significant impact, whereas PER exhibits a significant influence on stock prices. These results shed light on the financial factors that drive stock prices in the Food and Beverage industry and provide valuable insights for investors, practitioners, and policymakers alike. Highlights: Earnings Per Share (EPS) significantly influences stock prices in the Food and Beverage industry. Debt to Equity Ratio (DER) does not have a significant impact on stock prices in the sector. Price Earning Ratio (PER) exhibits a significant effect on stock prices in Food and Beverage companies. Keywords: Earnings Per Share, Debt to Equity Ratio, Price Earning Ratio, Stock Prices, Food and Beverage Industry.